PELATIHAN AKUNTANSI PADA PENGELOLAAN BANK SAMPAH “MENGUBAH SAMPAH MENJADI RUPIAH” - Zulfa Rosharlianti; Anisa Anisa; Wiwit Setyawati; Nurbaeti Nurbaeti; Novi Akhsani (Abdimisi, 2019)
Community service with the title Accounting Training in Management of Garbage Banks "Turning Trash Into Rupiah" aims to assist the management of Waste Bank in managing the records of the Garbage Bank and help resolve the problems of bookkeeping of the waste bank as faced today, including reports on purchases to customers of the waste bank , reports on sales to collectors, reports on the results of sales of garbage banks, reports on revenue and expenditure of funds and makes simple financial statements of waste banks as a responsibility of the management of the waste bank to the community. PKM involves lecturers and resource persons Lecturers in the S1 Accounting Study Program from Pamulang University. The results of the implementation of the PKM conducted on November 6, 2019 were adding knowledge in the field of accounting, especially regarding the financial recording of the participants of the Babakan Waste Management Group of Babakan Village, South Tangerang. The response of the participants was very good and happy because it was very helpful in learning about financial records. Suggestions submitted were PKM activities in the future to be carried out continuously so that the participants would always get guidance in accounting records and provide financial reporting to the public related to the Waste Bank, so that the community was more enthusiastic in collecting waste because it could provide high economic value. Keywords: Accounting Training, Trash Bank